Isolation and Genomic Characterization of an Acinetobacter johnsonii Bacteriophage AJO2 From Bulking Activated Sludge - Fan, Niansi; Yang, Min; Jin, Rencun; Qi, Rong (Frontiers in Microbiology, 2019)
A novel Podoviridae lytic phage AJO2, specifically infecting Acinetobacter johnsonii, was isolated from bulking activated sludge. The one-step growth experiment showed that the latent period and burst size of AJO2 were estimated to be 30 min and 78.1 phages per infected cell, respectively. The viability test indicated that neutral conditions (pH 6–8) were table for AJO2 survival, while it was sensitive to high temperature (≥60°C) and ultraviolet treatment (254 nm). Genomic sequencing revealed that the AJO2 had a linearly permuted, double-stranded (ds) DNA consisting of 38,124 bp, with the G+C content of 41 mol%. A total of 58 putative open reading frames (ORFs), 11 pairs of repeats and 11 promoters were identified. The AJO2 genome had a modular gene structure which shared some similarities to those of A. baumanii phages. However, genomic comparative analysis revealed many differences among them, and novel genes were identified in the AJO2 genome. These results contribute to subsequent researches on the interaction between bacteriophages and hosts in wastewater treatment, especially during the bulking period. Additionally, the newly isolated phage could be a good candidate as a therapeutic agent to control nosocomial infections caused by A. johnsonii.